Flood hydrograph reconstructing for Sarawak kanan river using infoworks river simulation (RS) - Mah, Yau Seng. (Universiti Malaysia Sarawak, UNIMAS, 2006)
Devastating floods in Sarawak KananRiver valley, particularly middle valley Bau area and downstream Siniawan in February 2003 and January 2004 indicated the need to study the flooding scenarios in the Sarawak Kanan River basin using state of the art modeling tools. The main purpose or this project is to develop a methodology to reconstruct flood events at Sarawak kananRiver to obtain flood hydrographs to provide explanation to the flooding of Bau and Siniawan.